Bacterial adhesion to poly‐(d, l)lactic acid blended with vitamin E: Toward gentle anti‐infective biomaterials. Issue 4 (4th August 2014) - Campoccia, Davide; Visai, Livia; Renò, Filippo; Cangini, Ilaria; Rizzi, Manuela; Poggi, Alessandro; Montanaro, Lucio; Rimondini, Lia; Arciola, Carla Renata
Abstract Anti‐infective properties of biomedical materials are often achieved by loading or coating them with powerful bactericides. Undesirably, these bioactive molecules can damage the host cells at the biomaterial‐tissues interface and, sometimes, even determine systemic toxic effects. The search for biomaterials able to actively resist infection while displaying a safe cytocompatibility profile toward eukaryotic cells is being progressively developed. Poly‐(d, l)lactic acid (PLA) is a broadly used resorbable material with established biocompatibility properties. The dissolving surfaces of a biodegradable material tend to be per se elusive for bacteria. Here, films of pristine PLA, of PLA blended with vitamin E (VitE) and PLA blended with vitamin E acetate (VitE ac) were challenged in vitro with the biofilm‐producers Staphylococcus epidermidis RP62A and Staphylococcus aureus ATCC25923. The bacterial adhesion properties of the different materials were investigated on small film disc specimens by a method based on microtiter plates. Adherent bacteria were quantified by both CFU plating and bioluminescence. Significant decrease in bacterial adhesion and biofilm accumulation was found on the surface of both the enriched polymers. These findings, together with the favorable intrinsic properties of PLA and the desirable bioactivities conferred by VitE, point up the VitE‐blended PLA polymers as gentle anti‐infective biomaterials. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 1447–1458, 2015.